2022
DOI: 10.1155/2022/9918215
|View full text |Cite
|
Sign up to set email alerts
|

Production of Chicken Patties Supplemented with Cantaloupe By-Products: Impact on the Quality, Storage Stability, and Antioxidant Activity

Abstract: This study investigated the effect of supplementation with cantaloupe peel (CP) and seeds (CS) (3, 6, 9, and 12%) powder on the quality and antioxidant activity of raw and cooked chicken patties during storage (-20°C/3 months). The addition of CP and CS powder increased protein, fat, ash, and fiber values of chicken patties compared with control, while carbohydrate, pH, and TBA were decreased at zero time and after 3 months of storage. The WHC, cooking yield, fat retention, and moisture retention were increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
2
1
0
Order By: Relevance
“…The highest diameter reduction was observed in the control sample, probably due to the shrinking of meat, denaturation of proteins, and water and fat loss. These results are in agreement with those of Ali et al, 2022 who reported that the lower shrinkage value was observed in the cantaloupe peel and seeds powder added patties.…”
Section: Cooking Properties and Functional Properties Of Chicken Nuggetssupporting
confidence: 93%
See 1 more Smart Citation
“…The highest diameter reduction was observed in the control sample, probably due to the shrinking of meat, denaturation of proteins, and water and fat loss. These results are in agreement with those of Ali et al, 2022 who reported that the lower shrinkage value was observed in the cantaloupe peel and seeds powder added patties.…”
Section: Cooking Properties and Functional Properties Of Chicken Nuggetssupporting
confidence: 93%
“…The highest moisture retention values were recorded in AC9 samples due to the higher fiber content of AC9. A similar result was reported by Ali et al, 2022 who reported that the cooking yields of chicken patties added cantaloupe peel and seeds powder were higher than the control samples at zero time. Chappalwar et al, 2021 also observed an increase in moisture and fat retention values of chicken patties with the addition of lemon albedo.…”
Section: Cooking Properties and Functional Properties Of Chicken Nuggetssupporting
confidence: 89%
“…Raw mutton patties were weighed, then cooked and surface‐dried with a filter and measured once more using an analytical scale balance (Ali et al., 2022). The cooking yield was calculated using the formula:Cooking yieldgoodbreak=Weight of cooked mutton pattiesWeight of0.25emraw0.25emmutton pattiesgoodbreak×100…”
Section: Methodsmentioning
confidence: 99%
“…Raw mutton patties were weighed, then cooked and surface‐dried with a filter and measured once more using an analytical scale balance (Ali et al., 2022 ). The cooking yield was calculated using the formula: …”
Section: Methodsmentioning
confidence: 99%
“…According to Alakali et al (2010), the occurrence of shrinkage during the cooking process was due to the muscle protein denaturation in the patties, and water and fat retention from the patties. With the addition of increased concentration of the treatments, the presence of fibre, solid or non-meat contents would create a stronger network and increase the ability of the patties to interact with water and fat, thus affecting the cooking yield and shrinkage of the food products (Hawashin et al, 2016;Sayas-Barberá et al, 2020;Ali et al, 2022). Despite no significant effects of the additives, the treated patties showed a slight increase in the cooking yield even with a low concentration of the treatments, suggesting the potential improvement for fat and fluid interaction in the patties incorporated with those treatments.…”
Section: Cooking Yield Cooking Shrinkage Moisture Content and Phmentioning
confidence: 99%